PENGUJIAN KOALISI DEBT TO EQUITY RATIO (DER) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM (STUDI KASUS EMPIRIS PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA) - Titin Hartini (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2017)
The objective of this research is to analyze the influence of Debt To Equity Ratio (DER) and Earning Per Share (EPS) on Stock Price in Food and Beverage Sector Manufacturing Companies Listed in ISSI Period 2012-2016. Data obtained from the Indonesian Stock Exchange (IDX) with the period of 2012 to 2016. The population of this study are 11 companies and the number of samples of 8 companies with passing through the purposive sample stage. Analytical techniques to be used in this study is multiple linear regression to obtain a comprehensive picture of the relationship between variables one with another variable. The results showed that Debt To Equity Ratio (DER) effect on Stock Price. Earning Per Share (EPS) effect on Stock Price in Manufacturing Company Food and Beverage Sector. The results of this study are expected that the variables Debt To Equity Ratio (DER) and Earning Per Share (EPS) can be used as guidance, either by the management company in the management of the company, or by investors in determining investment strategy.